Childhood Neurotoxicity and Brain Resilience to Adverse Events During Adulthood - Williams, AnnaLynn M. (Ann Neurol, 2020)
OBJECTIVE: To use childhood cancer survivors as a novel model to study whether children who experience central nervous system (CNS) injury are at higher risk for neurocognitive impairment associated with subsequent late onset chronic health conditions (CHC). METHODS: Adult survivors of childhood cancer (n=2,859, ≥10 years from diagnosis, ≥18 years old) completed a comprehensive neurocognitive battery and clinical exam. Neurocognitive impairment was defined as age-adjusted Z-score <10(th) percentile. Participants impaired on ≥3 tests had global impairment. CHC were graded using the Common Terminology Criteria for Adverse Events v4.3 (grade 1:mild, 2:moderate, 3:severe/disabling), 4:life-threatening), and were combined into a severity/burden score by frequency and grade (none/low, medium, high, and very high). 1,598 survivors received CNS directed therapy including cranial radiation, intrathecal methotrexate, or neurosurgery. Logistic regression estimated the odds of neurocognitive impairment associated with severity/burden score and grade 2–4 conditions, stratified by CNS treatment. RESULTS: CNS-treated survivors performed worse than non-CNS-treated survivors on all neurocognitive tests and were more likely to have global neurocognitive impairment (46.9% vs 35.3%, p<0.001). After adjusting for demographic and treatment factors, there was a dose-response association between severity/burden score and global neurocognitive impairment, but only among CNS-treated survivors (high OR=2.24, 95%CI 1.42–3.53; very high OR=4.07, 95%CI 2.30–7.17). Cardiovascular and pulmonary conditions were associated with processing speed, executive function, and memory impairments in CNS-treated but not non-CNS-treated survivors, who were impacted by neurologic conditions. INTERPRETATION: Reduced cognitive/brain reserve associated with CNS-directed therapy during childhood may make survivors vulnerable to adverse cognitive effects of cardiopulmonary conditions during adulthood.